A critical review of reductionist approaches for assessing the progress towards sustainability - Gasparatos, A; El-Haram, M; Horner, M (2008)
The increasing prominence of Sustainable Development as a policy objective has initiated a debate on appropriate frameworks and tools that will both provide guidance for a shift towards sustainability as well as a measure, preferably quantitative, of that shift. Sustainability assessment has thus the challenging task of capturing, addressing and suggesting solutions for a diverse set of issues that affect stakeholders with different values and span over different spatial and temporal scales. However sustainability assessment is still not a mature framework in the sense that Environmental Impact Assessment (EIA) and Strategic Environmental Assessment (SEA) are. This paper aims to provide suggestions for improving the sustainability evaluation part of a sustainability assessment. In particular it will provide a comprehensive review of different sustainability evaluation tools (from a reductionist perspective) as well as the feasibility of incorporating them within a sustainability assessment framework. Reviewed tools include monetary tools, biophysical models and sustainability indicators/composite indices that have been developed within different disciplines such as economics, statistics, ecology, engineering and town planning. © 2007 Elsevier Inc. All rights reserved.